Observed radiative cooling over the Tibetan Plateau for the past three decades driven by snow cover‐induced surface albedo anomaly. Issue 12 (21st June 2017) - Chen, Xiaona; Long, Di; Hong, Yang; Liang, Shunlin; Hou, Aizhong
Abstract: Seasonal snow cover on the Tibetan Plateau (TP) is a sensitive indicator of climate change. Unlike the decreasing snow cover extent and associated weakening of radiative cooling effects for the Northern Hemisphere during recent decades reported by previous studies, snow cover variability over the TP and its impact on the energy budget remain largely unknown. We defined the snow cover‐induced radiative forcing (Sn RF) as the instantaneous perturbation to Earth's shortwave radiation at the top of the atmosphere (TOA) induced by the presence of snow cover. Here using satellite observations and a radiative kernel approach, we found slightly enhanced Sn RF, i.e., a radiative cooling effect on the TP during the past three decades (1982–2014). However, this cooling effect weakened during 2001–2014 because of reduced snow cover at a rate of −0.61% decade −1 and land surface albedo at a rate of −0.72% decade −1 . Changes in snow cover fraction are highly correlated with anomalies in land surface albedo ( a s ) over the TP both spatially and temporally. Moreover, the Sn RF is closely related to the direct observation of TOA shortwave flux anomalies ( R 2 = 0.54, p = 0.004) over the TP during 2001–2014. Despite the insignificant interannual variability in Sn RF, its intra‐annual variability has intensified driven mostly by enhanced Sn RF during the snow accumulation season but weakened Sn RF during the melt season, indicating greater energy release during the transition between accumulation and melt seasons. This may pose a great challenge to snow meltwater use and flood prediction for transboundary rivers originating from the TP, such as the Brahmaputra River basin. Plain Language Summary: Despite many earlier related studies, snow cover variability and its effect on the energy budget for the Tibetan Plateau, as the Earth's third pole, remain largely unknown. In contrast to the generally accepted reduction over recent decades in the extent of snow cover in the Northern Hemisphere and the related decrease in radiative cooling effects reported in earlier works, using improved satellite observations, this study found enhanced radiative cooling over the Tibetan Plateau (TP) during 1982–2014, i.e., generally increased snow cover, particularly during the snow accumulation season. Improved understanding of such an effect is crucial to the sustainable utilization of snow meltwater and to the understanding of potential flooding risks over the lower reaches of the transboundary rivers originating on the TP. Key Points: Observed changes in SCF are highly correlated with anomalies in a s and streamflow observed at multiple gauging stations over the TP An enhanced Sn RF on the TP is found in the long term from 1982 to 2014, but this cooling effect weakened during 2001‐2014 Intra‐annual variability in Sn RF has intensified during the snow accumulation season but weakened in the melt season